The Role of Physical Literacy in the Association Between Weather and Physical Activity: A Longitudinal Multilevel Analysis With 951 Children - Carl, Johannes; Melby, Paulina S.; Kurtzhals, Mette L.; Nielsen, Glen; Bentsen, Peter; Elsborg, Peter (Journal of Physical Activity and Health, 2024)
Background: Numerous studies showed an effect of weather on physical activity (PA) levels in children. However, no study has yet examined the relevance of personal factors in this relationship. Therefore, this study analyzes (1) whether there are systematic interindividual differences in the extent to which weather affects the PA behavior and (2) whether physical literacy (PL) moderates the weather-PA association in children. Methods: A total of 951 children in 12 Danish schools (age 9.76 [1.59] y; 54.3% girls) completed objective PA assessments via accelerometry (moderate to vigorous PA, light PA, and sedentary behavior). Local weather data (precipitation, wind speed, temperature, and sunshine duration) were provided by the Danish Meteorological Institute. Participants' PL was measured employing the Danish version of the Canadian Assessment of Physical Literacy-2. The 4116 accelerometer days underwent longitudinal multilevel analyses while considering their nesting into pupils and school classes (n = 51). Results: Fluctuations in all PA indicators were significantly explained by variations in weather conditions, especially precipitation (P ≤.035). Significant interindividual differences were found for 9 of 12 analytical dimensions, suggesting that weather changes influence PA behavior differently across individuals (especially moderate to vigorous PA, χ2[4] ≥ 11.5, P ≤.021). However, PL moderated the relationship between weather and PA in only 2 of the 48 analytical constellations. Conclusions: Despite the varying impact of weather on PA across individuals, the present study favors a main effect model in which weather and PL exert independent effects on children's PA. The insufficient support for PL as a moderating factor calls for future studies to test alternative mechanisms in the weather-PA association.
CRIS-Team Scopus Importer:2024-07-19
Keywords: moderation; person; rain; sedentary behavior